Atopic dermatitis is associated with increased use of social benefits: a register‐based cohort study. (14th November 2019) - Slagor, R.M.; Nørreslet, L.B.; Ebbehøj, N.E.; Bonde, J.P.; Thomsen, S.F.; Agner, T.
Abstract: Background: The comprehensive consequences of atopic dermatitis (AD) include a negative influence on work life. However, data regarding use of social benefits in patients with AD are sparse. Objective: To examine the association between AD and use of social benefits, with a specific focus on paid sick leave and disability pension. Methods: The study cohort comprises citizens born in the period 1964–1999 with a diagnosis of AD registered in the Danish National Patient Registry (DNPR) and a 20‐fold match control group from the background population. Cross‐linkage of data from 1964 up to 2015 by four national registers (the DNPR; the Central Person Register; the Register of Medicinal Product Statistics; and the Danish Register for Evaluation of Marginalisation) enabled the comparison of AD patients and controls with respect to social benefits. Prescription of systemic medication served as a proxy for AD severity. Social benefits were analysed as a function of AD status using Cox regression. Results: A total of 28 156 AD patients were registered in the DNPR, and the control group comprised 473 836 individuals not registered with AD in the DNPR. AD was found to be associated with increased risk of receiving social benefits, paid sick leave in particular, and most pronounced for younger patients with severe AD (OR = 1.37, 95% CI: 1.25–1.52). The use of disability pension was increased for all groups of AD patients compared to controls and most pronounced for older patients with severe AD [HR 1.67 (95% CI: 1.45–1.93)]. Conclusion: Our data emphasize that AD significantly impacts work life negatively for the patients and is a financial burden for the society.